Columbia spotted frogs (Rana luteiventris) have characteristic skin microbiota that may be shaped by cutaneous skin peptides and the environment. Issue 10 (20th August 2020) - Loudon, A H; Kurtz, A; Esposito, E; Umile, T P; Minbiole, K P C; Parfrey, L W; Sheafor, B A
ABSTRACT: Global amphibian declines due to the fungal pathogen Batrachochytrium dendrobatidis ( Bd ) have led to questions about how amphibians defend themselves against skin diseases. A total of two amphibian defense mechanisms are antimicrobial peptides (AMPs), a component of amphibian innate immune defense and symbiotic skin bacteria, which can act in synergy. We characterized components of these factors in four populations of Columbia spotted frogs ( Rana luteiventris ) to investigate their role in disease defense. We surveyed the ability of their AMPs to inhibit Bd, skin bacterial community composition, skin metabolite profiles and presence and intensity of Bd infection. We found that AMPs from R. luteiventris inhibited Bd in bioassays, but inhibition did not correlate with Bd intensity on frogs. R. luteiventris had two prevalent and abundant core bacteria: Rhizobacter and Chryseobacterium. Rhizobacter relative abundance was negatively correlated with AMP's ability to inhibit Bd, but was not associated with Bd status itself. There was no relationship between metabolites and Bd . Bacterial communities and Bd differ by location, which suggests a strong environmental influence. R. luteiventris are dominated by consistent core bacteria, but also house transient bacteria that are site specific. Our emergent hypothesis is that host control and environmental factors shape the microbiota on R. luteiventris . Abstract : The authors surveyed the skin peptides, microbiota and metabolites from four environmentally distinct populations of Columbia spotted frogs to determine whether they are associated with each other and affect the occurrence of a fungal pathogen.